SARCOPENIA IN ELDERLY PATIENTS: WHAT ARE THE CONTRIBUTING RISK FACTORS? - Muhammad Raihan Afif Kurniawan; Nur Riviati; Bintang Arroyantri Prananjaya; Muhammad Reagan; Syarifah Aini (Fakultas Kedokteran Universitas Sriwijaya, 2024)
Sarcopenia in Elderly Patients: What are the Contributing Risk Factors?. Sarcopenia is the gradual loss of muscle mass associated with aging. The process by which sarcopenia occurs is not fully understood. Many factors are at risk of causing sarcopenia, such as age, gender, and physical activity. Early detection with the SARC-F questionnaire is needed to prevent sarcopenia. This study is a descriptive observational study with a cross-sectional approach with total sampling to see the description of sarcopenia and risk factors in elderly patients at the Geriatric Polyclinic of Dr. Mohammad Hoesin Hospital Palembang. Primary data were collected through interviews using a questionnaire, and then analyzed univariately. A total of 48.4% of the elderly at the Geriatric Polyclinic of Dr. Mohammad Hoesin Hospital Palembang had sarcopenia findings. Patients in the sarcopenia group were mostly aged 70-79 years (41.9%), female (64.5%), married (58.1%), history of primary education (32.3%), had worked (58.1%), had mild comorbidities (58.1%), sedentary physical activity (74.2%), and at risk of malnutrition (54.8%).